TARGETING MARKETS FOR EXPORT OF MACEDONIAN WINES TO THE EU - Ristevka-Jovanovska, Snezana; Sekovska, Blagica; Dimovska, Ana (Economics of Agriculture, 2018)
The Republic of Macedonia has all the prerequisites for pro duction of high quality wines and has great export potential, but Macedonian wines are almost unknown on the world wine market. Another problem is that most of the exported quantity is bulk wine, although in recent years the ratio be tween bulk and bottled wine started to change positively in terms of bottled wine. The wine market in the European Union is the most important export destination for Macedonian wines. Given the specificities of the wine market of in dividual member states, the aim of this paper is to select the countries in which the largest export of wine can be achieved. Macedonian wineries need to focus their export effort on the following markets: Germany, The Netherlands, Poland, Den mark and the Czech Republic. Methodology of desk research and market analysis is used for the conclusions.